Antioxidation and Melanogenesis Inhibition of Various Dendrobium tosaense Extracts - Chin-Feng Chan; Chin-Tung Wu; Wen-Ying Huang; Wen-Shin Lin; Han-Wei Wu; Teng-Kuan Huang; Min-Yun Chang; Yung-Sheng Lin (Molecules, 2018)
This study investigated the polyphenol content, antioxidant activity, and inhibition ability of mushroom tyrosinase and melanogenesis of Dendrobium tosaense (DT) extract. Ground DT was extracted using deionized water (W) or 50% ethanol (50E) at room temperature (RT) or 50 °C (50T) for 20 min. The 50T + 50E extract exhibited the highest total phenol content 47.0 ± 4.0 mg gallic acid equivalent/g DT extract, the highest level of 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) free-radical scavenging 66.0 ± 3.0 mg Trolox equivalent/g DT extract, and the highest reducing power 12.00 ± 0.50 mg vitamin C equivalent/g DT extract. The RT + W extract had the highest total flavonoid content 110.0 ± 3.0 mg quercetin equivalent/g DT extract. The RT + 50E extract had the lowest half maximal inhibitory concentration 1.30 ± 0.00 mg/mL for 2,2-diphenyl-1-picrylhydrazyl free-radical scavenging, and the lowest half maximal inhibitory concentration 6.40 ± 0.30 mg/mL for mushroom tyrosinase inhibition activity. DT extracts, especially RT + W and 50T + W, exhibited potent inhibitory effects on melanogenesis of B16/F10 cells. These results demonstrated the application potential of DT extract for skincare.